Addressing subjective experiences of sexuality-related social exclusion through education - Bytautas, Marius; Daukilas, Sigitas (Journal of Interdisciplinary Studies in Education, 2024)
Despite the prevailing perception that sexuality should be openly discussed, sexuality-related social exclusion persists, posing challenges for individuals. This mixed-methods study explores the perception of sexuality-related social exclusion experiences in young adults, identifying strategies within sexuality education that can mitigate these challenges. The study reveals that young adults who have and remember their social exclusion experiences tend to assign little significance to them when they perceive the reason for these experiences to be cultural rather than personal. In addition, gender-specific experiences of sexuality-related social exclusion are identified. The participants report feeling a lack of sexual communication with parents, friends, and romantic and sexual partners. The results suggest that parents are incapable of preventing sexuality-related social exclusion alone. Sexuality education emerges as a crucial tool in addressing these challenges.